The Contribution of Grade Point Average of Cum Laude Students to the Type and Relevancy of Career - Zulvia Trinova; Aprizal Ahmad (AT-TA'LIM, 2017)
The success of higher education institutions can be seen from several indicators. One of the indicators is the institutions that can produce outputs and outcomes with the competence in relation to the needs of society. The graduates’ academic achievement can be described through their grade point average (GPA). There were 79 graduates who got Cum Laude predicate at the Department of Islamic Studies, IAIN Imam Bonjol Padang in the 1st Period of graduation which was held on August to September and in the 2nd period on March, from the academic year of 2011 to 2015. The lowest GPA was 3.50 while the highest GPA was 3.93. The graduates who got Cum Laude have worked in several fields of jobs; such as Islamic Religion teachers, staffs in government offices, banks, and political parties both in West Sumatra and out of Sumatra. The study showed that there is no significant contribution of GPA with their career. It implied that GPA will not determine the graduate career either as a teacher on Islamic studies or as a teacher on social science and civics education. It also found that the graduates who work in out of field of studies were caused by the demand of the schools because of lack of teachers.